2013
DOI: 10.1155/2013/253408
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Subdural Hematoma after Spinal Anesthesia for Cesarean Section

Abstract: Intracranial subdural hematoma following spinal anesthesia is an infrequent occurrence in the obstetric population. Nevertheless, it is a potentially life-threatening complication. In the majority of the cases, the first clinical symptom associated with intracranial subdural bleeding is severe headache, but the clinical course may have different presentations. In this report, we describe the case of a 38-year-old woman with an acute intracranial subdural hematoma shortly after spinal anesthesia for cesarean se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…In our case there is a definite problem identified and successful treatment reversed the visual loss [13]. A case report of post spinal subdural hematoma has also been reported and evacuation was an effective treatment like in our case [14]. A case report by Mossallem noted diplopia as an early presenting sign for visual loss of increased pressure secondary to bilateral subdural hematoma [15].…”
Section: Discussionsupporting
confidence: 54%
“…In our case there is a definite problem identified and successful treatment reversed the visual loss [13]. A case report of post spinal subdural hematoma has also been reported and evacuation was an effective treatment like in our case [14]. A case report by Mossallem noted diplopia as an early presenting sign for visual loss of increased pressure secondary to bilateral subdural hematoma [15].…”
Section: Discussionsupporting
confidence: 54%
“…1 The accurate prevalence of subdural hematoma post lumbar puncture is inconclusive, probably due to delay in diagnosis, misdiagnosis, or under-reporting; however, some authors have reported an incidence of one in five million in obstetric procedures for this complication. 2,3 The clinical presentations of subdural hematoma depend on age, size, site, pace of formation of the blood collection, compression of intracranial structures, and clinical state of the patient. Usually, in the initial phase, symptoms may resemble that of post-dural puncture headache with postural changes related to low cerebrovascular fluid pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations ranging from alterations in headache from postural to non-postural, vomiting, diplopia, cognitive changes, changes in consciousness level, focal neurological signs like ptosis, paresis, weakness, and language deficits are also noted. 2,4,5 The period of headache triggered by subdural hematoma is categorized into three patterns. The first pattern, which is the most common, is a headache that presents early (within four days) after dural puncture and lingers with subsequent onset of subdural hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial hemorrhage following spinal or epidural anesthesia for obstetric or other anesthetic reasons has been reported with both large and small gauge needles, with patients ranging from young adult to elderly [ 4 ]. In many cases, the SDH was found after the sudden onset of a very severe, debilitating headache, occasionally with rapid neurologic decompensation [ 5 , 6 ]. However, Nepomuceno and Herd report a 17-year-old primigravida who suffered an inadvertent dural puncture during an attempt at epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%